Individual and environmental risk factors for post-traumatic stress among hospital nurses after the 2024 Noto Peninsula earthquake in Japan - Furutani, Naoki; Murata, Yuki; Miwa, Wataru; Nakamura, Masae; Nakajima-Ohyama, Kakusho C. (Frontiers in Psychiatry, 2025)
Although post-earthquake psychological distress arises from a complex interplay of personal vulnerabilities and environmental stressors, the pathways by which these factors interact remain underexplored. We surveyed 327 hospital nurses in Nanao City, Japan, approximately eight months after the magnitude-7.5 2024 Noto Peninsula earthquake; 224 complete responses were analyzed. Participants completed the Impact of Event Scale-Revised and a bespoke questionnaire assessing age, location during the earthquake, seven binary stress factors (home damage, relocation, community damage, change in co-residents, decline in family health, economic damage, earthquake-related sounds), and avoidant/emotion-focused coping. Analyses for each factor identified significant associations between IES-R scores and all stress factors except location during the earthquake and change in co-residents. ANCOVA adjusting for all predictors retained community damage, family health decline, economic damage, and coping as significant. Path analysis revealed two robust indirect pathways from age to distress: “age – community damage – IES-R” and “age – home damage – economic damage – IES-R”, plus a direct “age – intrusion” path. Decline in family health also influenced distress indirectly via economic loss. These findings demonstrate that older nurses’ elevated PTSS risk operates largely through greater exposure to specific disaster-related hardships, rather than age per se. Interventions should therefore combine individual support (e.g., coping skills, family health monitoring) with community-level recovery (e.g., infrastructure repair, social cohesion) to mitigate long-term mental-health impacts, especially among older adults.